Patient and Parent Satisfaction with a Dietitian-and Nurse-Led Celiac Disease Clinic for Children at the Stollery Children'S Hospital, Edmonton, Alberta. (2013) - Rajani, Seema; Sawyer-Bennett, Jessica; Shirton, Leanne; DeHaan, Gail; Kluthe, Cheryl; Persad, Rabindranath; Huynh, Hien Q; Turner, Justine
Abstract : OBJECTIVE: To assess patient and parent satisfaction with a primarily nurse- and dietitian-led celiac disease clinic in a tertiary pediatric centre. METHODS: An online survey was sent to families and patients attending the Stollery Children's Hospital's Multidisciplinary Pediatric Celiac Clinic (Edmonton, Alberta) since 2007. The survey focused on clinic attendance, satisfaction with clinic structure, processes, and education and preference for alternatives to the current process. Respondents were asked to rank satisfaction or preference on a five-point Likert scale, with 1 being lowest and 5 being highest. RESULTS: Most satisfaction related to follow-up with serology (4.6) and with a dietitian (4.3). The most preferred changes included either meeting the entire multidisciplinary team after the biopsy (4.7), or meeting with only the dietitian and nurse after the biopsy (4.4). The preferred education resources were the Internet (4.3) and the dietitian (4.2). The mean overall satisfaction score of the Multidisciplinary Pediatric Celiac Clinic was 4.0. CONCLUSIONS: Results of the present survey suggested that patients and families value a multidisciplinary follow-up clinic for children with celiac disease. In particular, feedback based on repeat blood work and regular contact with a dietitian were highly valued. The present survey, outlining the most valued aspects of the clinic, may be useful for service delivery in other regions. In addition, it provides information on how to better support pediatric patients with celiac disease.